2013
DOI: 10.1186/1471-2105-14-s2-s17
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive bi-level programming for optimal gene knockouts for targeted overproduction under phenotypic constraints

Abstract: BackgroundOptimization procedures to identify gene knockouts for targeted biochemical overproduction have been widely in use in modern metabolic engineering. Flux balance analysis (FBA) framework has provided conceptual simplifications for genome-scale dynamic analysis at steady states. Based on FBA, many current optimization methods for targeted bio-productions have been developed under the maximum cell growth assumption. The optimization problem to derive gene knockout strategies recently has been formulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…minimization of metabolic adjustment – MOMA) [72]. It has been suggested that mutant E.coli strains redistribute their metabolic fluxes in such way to minimally divert from the wild-type metabolic network [7274]. Our work is a comparable case, where the perturbation of the cells was not genetic, but kinetic, as a result of an intermittent substrate feeding.…”
Section: Resultsmentioning
confidence: 89%
“…minimization of metabolic adjustment – MOMA) [72]. It has been suggested that mutant E.coli strains redistribute their metabolic fluxes in such way to minimally divert from the wild-type metabolic network [7274]. Our work is a comparable case, where the perturbation of the cells was not genetic, but kinetic, as a result of an intermittent substrate feeding.…”
Section: Resultsmentioning
confidence: 89%
“…Table 1 also shows the comparison of experimental results for BAMOMA, OptKnock and MOMAKnock OptKnock had achieved succinate production of 6.21 mmol gDW -1 hr -1 which was the lower compared to BAMOMA with 8.1943 mmol gDW -1 hr -1 . Ren et al (2013) [15] proposed MOMAKnock as framework that identifies candidate knockout genes which leads to maximizing the production of targeted metabolite under MOMA assumption. MOMAKnock had obtained the production of 5.02 mmol gDW -1 hr -1 which was also lower compared to BAMOMA results.…”
Section: A Results and Discussion For Succinate Case Studymentioning
confidence: 99%
“…Let l i be the dimension of h i . The CP model defined in (25)(26)(27) is equivalent to the following single-level formulation. min cx…”
Section: Lemmamentioning
confidence: 99%
“…To address such challenge, many computational strategies and algorithms have been proposed, developed and investigated (see [16,4,13,30] and references therein), the vast majority of which, however, is devoted to solving the optimistic formulation. As a result, those advanced and capable computing tools strongly support the real applications of optimistic bilevel models in transportation planning and capacity expansion [7,25], government policy making [5,12], revenue management [8,14], electricity market [20,19] and computational biology [26,9].On the contrary, the pessimistic model is thought to be much more difficult than the optimistic one, and we generally believe that the solution methodologies developed for the latter one cannot be directly applied. Up to now, the pessimistic bilevel problem only receives a very limited amount of attention.…”
mentioning
confidence: 99%